Examining centrifugal pump BKS300 on cavitation - Fecser, Nikolett; Könözsy, László Z.; Ledos, Nicolas; Balázs, Sára (Hydraulics & Pneumatics Research Institute, 2020)
Pumps influence all our lives directly or indirectly. Pumps are one of the most widespread types of turbomachines. Their task is to pump fluid from one place to another and engineers who are experts in pump technologies are familiar with the phenomenon of cavitation. The present work focuses on the cavitation from an experimental point-of-view. Measurements have been carried out on the type of a centrifugal pump. A polynomial fitting method has been developed and a semi-empirical formula has been proposed. Furthermore, numerical simulations have been performed for modelling two-phase cavitating turbulent flows in the investigated centrifugal pump. The objective of this study is to bring attention to cavitation and contribute to the knowledge in terms of its harmful effects
Keywords: centrifugual pump; measurement; cavitation; Fluid; Pumps